2017
DOI: 10.1103/physrevmaterials.1.023603
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elasticity in rocks: A comprehensive three-dimensional description

Abstract: We study theoretically and experimentally the mechanisms of nonlinear and nonequilibrium dynamics in geomaterials through dynamic acoustoelasticity testing. In the proposed theoretical formulation, the classical theory of nonlinear elasticity is extended to include the effects of conditioning. This formulation is adapted to the context of dynamic acoustoelasticity testing in which a low-frequency "pump" wave induces a strain field in the sample and modulates the propagation of a high-frequency "probe" wave. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Since M l has different sign for compression and dilation, it must result from compression and it should thus disappear for shear excitation. This was indeed observed by Lott et al (2017) as vanishing of the fundamental frequency component for shear excitation.…”
Section: Model Parameterssupporting
confidence: 55%
See 2 more Smart Citations
“…Since M l has different sign for compression and dilation, it must result from compression and it should thus disappear for shear excitation. This was indeed observed by Lott et al (2017) as vanishing of the fundamental frequency component for shear excitation.…”
Section: Model Parameterssupporting
confidence: 55%
“…A series of DAET experiments investigated the detailed nonlinear behaviour of different rocks (Renaud et al 2012(Renaud et al , 2013Rivière et al 2013Rivière et al , 2015. Longitudinal, shear (Lott et al 2017) and complex flexural deformation from impacts (Eiras et al 2016) have been used as excitation. The response of a single fatigue crack was investigated (Rivière et al 2014) as well as the in situ nonlinearity of soil on the scale of metres using seismic equipment and a vibrator truck (Renaud et al 2014).…”
Section: Daet Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was later confirmed by an independent set of experiments where it was demonstrated that, given appropriate corrections to account for the fact that the pump and the probe are in orthogonal directions, the material softening obtained from DAET in the conditioning phase is equivalent to that obtained from NRUS (Lott et al, ). Last, Lott et al () demonstrated experimentally that there are additional subtleties to consider that are related to the type of strain field induced by the LF pump (e.g., axial motion versus torsional motion) and the type of waves used as HF probes (e.g., P waves and S waves with various polarizations).…”
Section: Introductionmentioning
confidence: 99%
“…Memory effects are peculiar of hysteretic elastic media [7,8,34,35] and consist in the following. When a sample is excited at a fixed (high) amplitude of excitation, transition to a nonequilibrium state is observed (conditioning), which is manifested by a not instantaneous change of both velocity and damping.…”
Section: B Conditioning and Relaxationmentioning
confidence: 99%